The 7 Non-negotiables of winning : - David K. Williams (John Wiley & Sons, Inc, 2013)
The 7 Non-Negotiables of Winning looks beyond employee skills and background and to identify the true game-changing character traits for creating a winning culture. Based on the author's methodology for what abilities drive decisions and actions within his own company, The 7 Non-Negotiables of Winning details how respect, belief, loyalty, commitment, trust, courage, and gratitude play an integral part to multiple key business outcomes.